Tort - Turner, Chris (London : Hodder & Stoughton, 2001)
Key Facts is a new series specially written for law students. It provides revision tools for a broad range of law courses from A level to degree level. This text covers tort.
Includes index.
Keywords: Torts -- England; Torts -- Wales; Advice and Rights